Prefrontal cortex activation during story encoding/retrieval: a multi-channel functional near-infrared spectroscopy study - Basso Moro, Sara; Cutini, Simone; Ursini, Maria Laura; Ferrari, Marco; Quaresima, Valentina (Frontiers in Human Neuroscience, 2013)
Encoding, storage and retrieval constitute three fundamental stages in information processing and memory. They allow for the creation of new memory traces, the maintenance and the consolidation of these traces over time, and the access and recover of the stored information from short or long-term memory. Functional near-infrared spectroscopy (fNIRS) is a non-invasive neuroimaging technique that measures concentration changes of oxygenated-hemoglobin (O2Hb) and deoxygenated-hemoglobin (HHb) in cortical microcirculation blood vessels by means of the characteristic absorption spectra of hemoglobin in the near-infrared range. In the present study, we monitored, using a sixteen-channel fNIRS system, the hemodynamic response during the encoding and retrieval processes (EP and RP, respectively) over the prefrontal cortex (PFC) of thirteen healthy subjects (27.2±2.6 y.) while were performing the “Logical Memory Test” (LMT) of the Wechsler Memory Scale. A LMT-related PFC activation was expected; specifically, it was hypothesized a neural dissociation between EP and RP. The results showed a heterogeneous O2Hb/HHb response over the mapped area during the EP and the RP, with a O2Hb progressive and prominent increment in ventrolateral PFC since the beginning of the EP. During the RP a broader activation, including the ventrolateral PFC, the dorsolateral PFC and the frontopolar cortex, was observed. This could be explained by the different contributions of the PFC regions in the EP and the RP. Considering the fNIRS applicability for the hemodynamic monitoring during the LMT performance, this study has demonstrated that fNIRS could be utilized as a valuable clinical diagnostic tool, and that it has the potential to be adopted in patients with cognitive disorders or slight working memory deficits.